Factors associated with student engagement in a selected private university in Malaysia - Chan, Wan Ling (2014)
This study used the Theory of Planned Behavior to explore university students’ intention to engage in premarital sexual behavior. Student engagement in the context of this study referred to the engagement of premarital sexual behavior. The factors being studied are attitude, subjective norm and perceived behavioral control. This study adopted a correlational survey research method involving 375 university students from a selected university in Malaysia, respondents were selected through stratified cluster sampling. Analyses employed in this study are descriptive analysis,Pearson Product Moment Correlation and Multiple Regression. Results showed that 10.7 percent of the respondents have had sexual intercourse experience before. Pearson Product Moment Correlation analysis concluded that all the three factors investigated in the study, which attitudes, subjective norms and perceived behavioral control are associated with respondents’ premarital sexual behavior intention. Among the factors,attitude appeared to be the strongest predictor for premarital sexual behavior intention. This conclusion was obtained through Multiple Regression test. Overall, Theory of Planned Behavior is proven to be a suitable model to explain premarital sexual behavior for youth in Malaysia. Results of this study highlighted the importance of designing appropriate sex education or sexual and reproductive health program as an intervention effort to improve sexual health among Malaysian university youth. Theory of Planned Behavior can be used as a reference in designing the program. Researcher also recommends for replication of study to be done in the future in order to understand deeper about Malaysian students’ premarital sexual prevalence and factors associated with the behavior.